2021
DOI: 10.3390/ma14154330
|View full text |Cite
|
Sign up to set email alerts
|

Novel HMO-Glasses with Sb2O3 and TeO2 for Nuclear Radiation Shielding Purposes: A Comparative Analysis with Traditional and Novel Shields

Abstract: The radiation shielding characteristics of samples from two TeO2 and Sb2O3-based basic glass groups were investigated in this research. TeO2 and Sb2O3-based glasses were determined in the research as six samples with a composition of 10WO3-(x)MoO3-(90 − x)(TeO2/Sb2O3) (x = 10, 20, 30). A general purpose MCNPX Monte Carlo code and Phy-X/PSD platform were used to estimate the radiation shielding characteristics. Accordingly, the linear and mass attenuation coefficients, half value layer, mean free path, variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Table 2 shows HVL and MFP which is important quantities that describe the effectiveness of radiation shielding 56 . HVL represents the thickness of the sample which reduces the initial intensity of the photons by half, and MFP is the distance between two collisions when the photon traveled before scattering or absorption occurs 57 , 58 . The lower HVL and MFP value indicated good in absorbing radiation of the shield, which determined by 59 , 60 : …”
Section: Results and Discassionmentioning
confidence: 99%
“…Table 2 shows HVL and MFP which is important quantities that describe the effectiveness of radiation shielding 56 . HVL represents the thickness of the sample which reduces the initial intensity of the photons by half, and MFP is the distance between two collisions when the photon traveled before scattering or absorption occurs 57 , 58 . The lower HVL and MFP value indicated good in absorbing radiation of the shield, which determined by 59 , 60 : …”
Section: Results and Discassionmentioning
confidence: 99%
“…However, our findings showed that the S3 sample has the highest linear and mass attenuation coefficients at all the gamma-ray energies studied. Calculating the half-value layer (HVL) of a shielding material is a critical way for determining its effectiveness against the radiation being employed [51,52].…”
Section: Resultsmentioning
confidence: 99%
“…In the quest for more versatile shielding solutions, the industry focuses on developing transparent materials that can offer robust defense against gamma and X-rays. Such materials are in high demand within nuclear medicine and diagnostic imaging [5][6][7].…”
Section: Research Articlementioning
confidence: 99%